An update on diagnosis and treatments of childhood interstitial lung diseases - Marczak, Honorata; Krenke, Katarzyna; Griese, Matthias; Carlens, Julia; Seidl, Elias; Gilbert, Carlee; Emiralioglu, Nagehan; Torrent-Vernetta, Alba; Willemse, Brigitte; Epaud, Ralph; Delestrain, Celine; Louvrier, Camille; et al. (Breathe (Sheffield, England), 2025)
Childhood interstitial lung diseases (chILDs) are rare and heterogeneous disorders associated with significant morbidity and mortality. The clinical presentation of chILD typically includes chronic or recurrent respiratory signs and symptoms with diffuse radiographic abnormalities on chest imaging. Diagnosis requires a structured, multi-step approach. Treatment options are limited, with disease-specific therapies available only in selected cases and management relying primarily on supportive care. Awareness of chILDs has been steadily increasing. New diagnoses, advanced diagnostic tests, and novel treatments are emerging each year, highlighting the importance of collaborative, multidisciplinary teams in providing comprehensive care for children and families affected by these complex conditions. On behalf of the European Respiratory Society Clinical Research Collaboration for chILD (ERS CRC chILD-EU), this review provides an updated overview of the diagnostic approach and management strategies for chILDs.